Pengaruh Kualitas Pelayanan dan Customer Relationship Management Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Pelabuhan Cigading – PT Krakatau Bandar Samudera) - Budiyanto, Guntur Arief; Surya, Djasuro (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2019)
This research is due to the decreasing of cargo dry service in Cigading port which caused high queue and potency to make customers move to other port. The purpose of this study is to determine the effect of service quality and customer relationship management on customer loyalty through customer satisfaction as intervening variable. The study was conducted on 30 companies of Cargo Dry service users in Port Cigading with the number of sample units taken as many as 60 respondents. Data analysis using SEM-PLS method. The result of hypothesis test shows that there is positive and significant influence of service quality to customer satisfaction and customer loyalty, there is positive and significant influence of CRM to customer satisfaction and customer loyalty, and no influence of customer satisfaction to customer loyalty. Customer satisfaction does not prove to be an intervening between service quality and CRM to customer loyalty